PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATA PELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN SISWA KELAS IV SDN 2 MANTINGAN - RIA WIDYASWATI; MARIA AGUSTINA AMELIA; MARCIANA SARWI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The background of this research is the learning outcomes and learning activities of fourth grade students of SDN 2 Mantingan in social studies subjects are low so it requires improvements to improve learning outcomes and active learning of fourth grade students of SDN 2 Mantingan in social studies subjects. The purpose of this study was to find out the improvement of learning outcomes and active learning of fourth grade students of SDN 2 Mantingan in social studies subjects using a problem based learning model. The type of research used is classroom action research. This research was conducted at SDN 2 Mantingan with a total of 32 research subjects. Data collection techniques used are tests and observations. The validity of the data used is expert judgment. The results showed that the use of problem based learning models could improve learning outcomes and active learning of fourth grade students at SDN 2 Mantingan in social studies subjects. In the pre-cycle the average value obtained by students was 62.84 with a classical completeness of 31.25%. Then in the first cycle the average value obtained by students is 74.21 with classical completeness 32.14%. From the pre-cycle to the first cycle there was an increase in the average value of student learning outcomes which was 11.37 and an increase in classical completeness 0.89%. In the second cycle, the average score obtained by the students was 75.34 with a classical completeness of 84.61%. From cycle I to cycle II there was an increase in the average score of 1.13 and an increase in classical completeness as much as 52.47%. The average value of student activity in the pre-cycle is 46.15% and is included in the criteria for being very less active. In the first cycle, the average value of student learning activity was 71.78% and was included in the criteria for being quite active. From the pre-cycle to the first cycle, there was an increase in learning outcomes as much as 25.63%. In cycle II, the average value of student learning activity is 86.92% and is included in the very active criteria. From cycle I to cycle II there was an increase of 15.14%. ABSTRAKLatar belakang dari penelitian ini adalah hasil belajar dan kekatifan belajar siswa kelas IV SDN 2 Mantingan pada mata pelajaran IPS termasuk rendah sehingga memerlukan perbaikan untuk menigkatkan hasil belajar dan keaktifan belajar siswa kelas IV SDN 2 Mantingan pada mata pelajaran IPS. Tujuan dari penelitian ini adalah untuk menegtahui peningkatan hasil belajar dan keaktifan belajar siswa kelas IV SDN 2 Mantingan pada mata pelajaran IPS dengan menggunakan model problem based learning. Jenis penelitian yang digunakan adalah penelitian tindakan kelas. Penelitian ini dilaksanakan di SDN 2 Mantingan dengan jumlah subjek penelitian sebanyak 32 orang. Teknik pengumpulan data yang digunakan adalah tes dan observasi. Validitas data yang digunakan adalah expert judgment. Hasil penelitian menunjukkan bahwa penggunaan model problem based learning dapat meningkatkan hasil belajar dan keaktifan belajar siswa kelas IV SDN 2 Mantingan pada mata pelajaran IPS. Pada pra siklus nilai rata-rata yang diperoleh siswa adalah 62,84 dengan ketuntasan klasikal 31,25%. Kemudian pada siklus I nilai rata-rata yang diperoleh siswa adalah adalah 74,21 dengan ketuntasan klasikal 32,14%. Dari pra siklus ke siklus I terjadi peningkatan nilai rata-rata hasil belajar siswa adalah 11,37 dan peningkatan ketuntasan klasikal 0,89%. Pada siklus II nilai rata-rata yang dipeorleh siswa adalah 75,34 dengan ketuntasan klasikal 84,61%. Dari siklus I ke siklus II terjadi peningkatan nilai rata-rata sebanyak 1,13 dan peningkatan ketuntasan klasikal sebanyak 52,47%. Nilai rata-rata kekatifan siswa pada pra siklus adalah 46,15% dan masuk dalam kriteria sangat kurang aktif. Pada siklus I nilai rata-rata keaktifan belajar siswa adalah 71,78% dan masuk dalam kriteria cukup aktif. Dari pra siklus ke siklus I terjadi peningkatan hasil belajar sebanyak 25,63%. Pada siklus II nilai rata-rata keaktifan belajar siswa adalah 86,92% dan masuk dalam kriteria sangat aktif. Dari siklus I ke siklus II terjadi peningkatan sebanyak 15,14%.